The relationship between sex hormones and the metabolic syndrome - Lunenfeld, Bruno (Acta Biomedica Atenei Parmensis, 2010)
Given the fundamental role of sex hormones in the regulation of body composition and homeostasis, in humans, more emphasis should be placed on the potential role of androgen dysregulation in the pathophysiology of different obesity phenotypes and the metabolic syndrome (MetS). Physicians must be mindful to evaluate MetS in all men diagnosed with hypogonadism and hypogonadism in all men diagnosed with MetS. Thus, clinical screening for obese patients should include the assessment of waist circumference, testosterone levels, body mass index and physical inactivity. The side effects of Androgen deprivation therapy (ADT) for prostate cancer patients may delay mortality from prostate cancer but , it is undeniable that the effects induced by this treatment have serious consequences. ADT should be considered and discussed between physicians and patients when making treatment decisions. If the decision is to initiate ADT, proper monitoring, preventive strategies and management of weight, insulin resistance, diabetes hyperlipidemia, sexual function and Osteopenia is essential.